MERANCANG PEMBELAJARAN DARING BAGI ANAK USIA DINI - Yuyun Istiana (Universitas Islam Lamongan, 2021)
s the Covid-19 pandemic escalated in early 2020, Indonesia suspended all activities in school. Approximately 45 million students in Indonesia were unable to attend schools, including early childhood students. As a result, the Indonesian government encourages learning activities to be carried out online or remotely. This study aims to develop a framework that can be used in online learning for early childhood in Indonesia during the Covid-19 pandemic. The methodology used is a literature study on online learning in early childhood, which includes literature review and empirical research. Online learning in Indonesia is faced with various challenges, such as the disparity in the quality of education in Java and outside Java, uneven internet access, and lack of ICT skills raise concerns over the quality of online learning being implemented across the nation. From the perspective of early childhood education, online learning is relatively new. There are only a few research studies that identify effective practices for online learning for early childhood. It can also be challenging for teachers who new to online learning to choose what strategies work best or where to start. Moreover, there is a heated debate about whether online learning is appropriate for early childhood. Despite all these limitations and debates, this study proposes a framework in online learning which focuses more on the pedagogical aspects rather than the technological aspects.